Avia Pasay intergrated cultural and community hub - Bonula, Cristina Joy A. (College of Architecture, University of the Philippines Diliman, 2018)
Aviation industries are vital to the Philippines. It is one of the sectors which supports over 1.2 million jobs. Likewise, they contribute significantly to the Gross Domestic Product of many developed countries. In the Philippines, Pasay City is known as the travel and convention city of Metro Manila. As the gateway to the Philippines, it has the enviable distinction of being the country's prime aviation hub being host to the NAIA terminals. However, the social and economic benefits of air transport are at risk if the key issues are not addressed. Through this project, the Avia center, is realized to provide architectural solutions in creating community-oriented learning environment for professional and ordinary Filipino gearing towards global competence. It is also aimed to be a creative exhibition space promoting aviation supplemented with recreational and commercial spaces for the community. As it is strategically located near the airport area along with the residential areas, the center sit accessible to its possible market. The center aims to develop the community and include them in the growing industry of the city. As such, the building shall provide spaces and facilities for aviation research and training centers, as well as other collaborative spaces that will improve the life in the community. Being more than just a building, it could be also a place where people would want to work to live and enjoy all aspects of their lives and create a community that people wanted to be part of.